Determining the prevalence of drug and alcohol misuse in an acute mental health setting - Heslop, K.; Wynaden, Dianne (Wiley-Blackwell Publishing Asia, 2014)
This presentation reports on the prevalence of substance use of 695 patients with mental illnesses admitted to an inner city acute mental health unit over a 14 month period. Data collected was obtained from routine screening for drug and alcohol on admission to the acute mental health unit using the World Health Organisation (WHO) Alcohol Smoking and Substance Involvement Screening Test (ASSIST). A review of the data identified that the substances most frequently used were tobacco, alcohol and cannabis. Appropriate assessment of substance use, recognition of addictive behaviours, withdrawal management that includes appropriate pharmacological intervention and supportive counselling that is initiated in the acute mental health setting and continued post discharge are likely to be the most beneficial interventions to reduce the frequency of substance use and the harms associated with tobacco, alcohol and cannabis use in people with mental illness.